CD34+VEGFR‐3+ progenitor cells have a potential to differentiate towards lymphatic endothelial cells. Issue 3 (22nd January 2014) - Tan, Yu‐zhen; Wang, Hai‐jie; Zhang, Mei‐hua; Quan, Zhe; Li, Ting; He, Qi‐zhi
Abstract Endothelial progenitor cells (EPCs) play an important role in postnatal neovascularization. However, it is poorly understood whether EPCs contribute to lymphangiogenesis. Here, we assessed differentiation of a novel population of EPCs towards lymphatic endothelial cells and their lymphatic formation. CD34+VEGFR‐3+ EPCs were isolated from mononuclear cells of human cord blood by fluorescence‐activated cell sorting. These cells expressed CD133 and displayed the phenotype of the endothelial cells. Cell colonies appeared at 7–10 days after incubation. The cells of the colonies grew rapidly and could be repeatedly subcultured. After induction with VEGF‐C for 2 weeks, CD34+VEGFR‐3+ EPCs could differentiate into lymphatic endothelial cells expressing specific markers 5′‐nucleotidase, LYVE‐1 and Prox‐1. The cells also expressed hyaluronan receptor CD44. The differentiated cells had properties of proliferation, migration and formation of lymphatic capillary‐like structures in three‐dimensional collagen gel and Matrigel. VEGF‐C enhanced VEGFR‐3 mRNA expression. After interfering with VEGFR‐3 siRNA, the effects of VEGF‐C were diminished. These results demonstrate that there is a population of CD34+VEGFR‐3+ EPCs with lymphatic potential in human cord blood. VEGF‐C/VEGFR‐3 signalling pathway mediates differentiation of CD34+VEGFR‐3+ EPCs towards lymphatic endothelial cells and lymphangiogenesis. Cord blood‐derived CD34+VEGFR‐3+ EPCs may be a reliable source in transplantation therapy for lymphatic regenerative diseases.